Comparing Biomarkers for Predicting Pathological Responses to Neoadjuvant Therapy in HER2-Positive Breast Cancer: A Systematic Review and Meta-Analysis - Zhao, Fuxing; Huo, Xingfa; Wang, Miaozhou; Liu, Zhen; Zhao, Yi; Ren, Dengfeng; Xie, Qiqi; Liu, Zhilin; Li, Zitao; Du, Feng; Shen, Guoshuang; Zhao, Jiuda (Frontiers in Oncology, 2021)
Introduction The predictive strength and accuracy of some biomarkers for the pathological complete response (pCR) to neoadjuvant therapy for HER2-positive breast cancer remain unclear. This study aimed to compare the accuracy of the HER2-enriched subtype and the presence of PIK3CA mutations, TILs, HRs, and Ki-67 in predicting the pCR to HER2-positive breast cancer therapy. Methods We screened studies that included pCR predicted by one of the following biomarkers: the HER2-enriched subtype and the presence of PIK3CA mutations, TILs, HRs, or Ki-67. We then calculated the pooled sensitivity, specificity, positive and negative predictive values (PPVs and NPVs, respectively), and positive and negative likelihood ratios (LRs). SROC curves and AUCs were used to estimate the diagnostic accuracy. Results The pooled estimates of sensitivity and specificity for the HER2-enriched subtype and the presence of PIK3CA mutations, TILs, HRs, and Ki-67 were 0.66 and 0.62, 0.85 and 0.27, 0.49 and 0.61, 0.54 and 0.64, and 0.68 and 0.51, respectively. The AUC of HER2-enriched subtype was significantly higher (0.71) than those of the presence of TILs (0.59, P = 0.003), HRs (0.65, P = 0.003), and Ki-67 (0.62, P = 0.005). The AUC of HER2-enriched subtype had a tendency to be higher than that of the presence of PIK3CA mutations (0.58, P = 0.220). Moreover, it had relatively high PPV (0.58) and LR+ (1.77), similar NPV (0.73), and low LR− (0.54) compared with the other four biomarkers. Conclusions The HER2-enriched subtype has a moderate breast cancer diagnostic accuracy, which is better than those of the presence of PIK3CA mutations, TILs, HRs, and Ki-67.